2020
DOI: 10.1101/2020.06.02.20120394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Swab Tests to Decrease the Stress by COVID-19 on the Health System using AI, MLR & Statistical Analysis

Abstract: Objectives: The outbreak of the new Coronavirus (COVID-19) pandemic has prompted investigations on various aspects. This research aims to study the possible correlation between the numbers of swab tests and confirmed cases of infection, with special attention to the sickness level. Study Design: The study is carried out with reference to the Italian case, but the result is of more general importance, in particular for countries with limited availability of ICUs (intensive care units). Methods: The statistica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Pirouz and Violini (2020), analyzed the outbreak patterns of COVID-19 by analysis of 117 countries. They suggested two mechanisms of triggering the development of the infection, namely the normal spread of an infection from one parent case and the consequence of a unique phenomenon of accumulation of contagious people [22].…”
Section: Introductionmentioning
confidence: 99%
“…Pirouz and Violini (2020), analyzed the outbreak patterns of COVID-19 by analysis of 117 countries. They suggested two mechanisms of triggering the development of the infection, namely the normal spread of an infection from one parent case and the consequence of a unique phenomenon of accumulation of contagious people [22].…”
Section: Introductionmentioning
confidence: 99%
“…To predict epidemiological examples of COVID-19 cases in India, this study used MLP, vector auto-regression, and linear regression methods using COVID-19 data. Statistical analysis demonstrated a correlation that exists between the swab tests numbers and mild cases admitted to hospital, daily positive cases, recovery, intensive care cases, and death rate, which provided the foundation for an AI study [78]. A multivariate linear regression (MLR) method was used for results validation.…”
Section: Methodsmentioning
confidence: 99%
“…To suppress the pandemic, a prompt action in identifying the suspected cases is important. In order to study the correlation between the number of swab tests and confirmed cases of infection, with attention to the sickness level, AI approaches are used in [513] . The authors report that there is correlation between the number of swab tests and daily positive cases, mild cases admitted to hospital, intensive care cases, recovery and death rates.…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%